Exploring the faint source population at 15.7 GHz - Whittam, I; Riley, J; Green, D; Jarvis, M (International School for Advanced Studies (Trieste), 2015)
We discuss our current understanding of the nature of the faint, high-frequency radio sky. The Tenth Cambridge (10C) survey at 15.7 GHz is the deepest high-frequency radio survey to date, covering 12 square degrees to a completeness limit of 0.5 mJy, making it the ideal starting point from which to study this population. In this work we have matched the 10C survey to several lower-frequency radio catalogues and a wide range of multi-wavelength data (near- and far-infrared, optical and X-ray). We find a significant increase in the proportion of flat-spectrum sources at flux densities below 1 mJy - the median radio spectral index between 15.7 GHz and 610 MHz changes from 0.75 for flux densities greater than 1.5 mJy to 0.08 for flux densities less than 0.8 mJy. The multi-wavelength analysis shows that the vast majority (> 94 percent) of the 10C sources are radio galaxies; it is therefore likely that these faint, flat spectrum sources are a result of the cores of radio galaxies becoming dominant at high frequencies. We have used new observations to extend this study to even fainter flux densities, calculating the 15.7-GHz radio source count down to 0.1 mJy, a factor of five deeper than previous studies. There is no evidence for a new population of sources, showing that the high-frequency sky continues to be dominated by radio galaxies down to at least 0.1 mJy.